PERILAKU HIDUP SEHAT CERDIK PATUH CEGAH DAN KENDALIKAN HIPERTENSI - Ratna Dian Kurniawati; Yakobus Sinaga; Nabilah Nuur Fajr; Fathiya Insania; Fenty Nurohmah; Fikran Hafizh Rasyadi; Riska Riska; Fitrina Khoerunnisa (Jurnal Abdi Insani, 2023)
Hypertension, which is widely known as high blood pressure, is still a health challenge in the post-Covid-19 era. The stress and anxiety associated with a pandemic can directly increase the risk of hypertension. As a silent killer, hypertension is often asymptomatic. Plus an instant lifestyle, lack of physical activity (sedentary lifestyle), stress, working from home, mental health disorders and chronic anxiety. This community service aims to make health efforts in the prevention and control of hypertension through increasing public knowledge about the importance of healthy living behavior in preventing and controlling hypertension. This community service method is a series of interventions in the form of health efforts including the Community Rukun Warga (MMRW) Consultation, counseling on prevention of hypertension control, Smart Quiz Competition for Smart Edges of Hypertension, obedience training in Independent Blood Pressure Control with a digital sphygmomanometer, special exercises for hypertension and installation of posters at the Community Health Center, Poskesdes, Posyandu and the Cihanyir Village Multipurpose Center. After participating in a series of intervention activities in community service related to the prevention and control of hypertension, it was found that all residents of RW 03 Cihangir had good knowledge (100%). In carrying out the community service, the residents of RW 03 Cihanyir are very enthusiastic and respond to every activity carried out. Achievement of all series of health efforts in community service related to hypertension prevention through increasing public knowledge about the importance of healthy living behavior in preventing and controlling hypertension. The need for follow-up through cross-sector and cross-program collaboration under the guidance and guidance of the Cihanyir Health Center.